Bryant's style - Ewalt, Cora Elizabeth (My University, 1898)
Introduction: The birthplace of William Cullen Bryant seems to have been selected by Nature as a fit residence for the early unfolding of high poetic genius. The little town of Cunnington situated on the forest elevations about the beautiful valley of the Connecticut in the old country of Campshire, has the distinction of giving birth to the greatest poet of America.
Citation: Ewalt, Cora Elizabeth. Bryant's style. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: William Cullen Bryant; Poetic Genius; Nature; Theses; Manuscripts (documents)